2018
DOI: 10.3389/feart.2018.00077
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Core Formation in Terrestrial Planets by Percolative Flow: In-Situ Imaging of Metallic Melt Migration Under High Pressure/Temperature Conditions

Abstract: Core formation has left a lasting geochemical signature on the Earth. In order to constrain the composition of the Earth we must fully understand the processes by which newly formed Earth, and the bodies which accreted to it, differentiated. Percolation of iron-rich melt through solid silicate has been invoked as a mechanism for differentiation and core formation in terrestrial bodies in the early solar system. However, to date the contribution of percolation to core formation cannot be assessed due to the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…While previous models have suggested that the metal may have an internal source (eg., the molten core of the planetesimal, suggested by a ferrovolcanism origin; Johnson et al, 2020), recent isotopic studies show a statistically significant disequilibrium between the metal and silicate phases in pallasites, strengthening the argument for an external source delivered via impact (Windmill et al, 2022). Studies of core formation via percolative flow Berg et al, 2018) and intrusion propagation and emplacement alongside microstructural evidence from pallasite samples can be utilised to better understand this. Our model can aid in this research, as it provides a range of mantle temperatures over which pallasite-like textures can be produced.…”
Section: Discussionmentioning
confidence: 98%
“…While previous models have suggested that the metal may have an internal source (eg., the molten core of the planetesimal, suggested by a ferrovolcanism origin; Johnson et al, 2020), recent isotopic studies show a statistically significant disequilibrium between the metal and silicate phases in pallasites, strengthening the argument for an external source delivered via impact (Windmill et al, 2022). Studies of core formation via percolative flow Berg et al, 2018) and intrusion propagation and emplacement alongside microstructural evidence from pallasite samples can be utilised to better understand this. Our model can aid in this research, as it provides a range of mantle temperatures over which pallasite-like textures can be produced.…”
Section: Discussionmentioning
confidence: 98%
“…where d is grain size and C is a constant that depends on the melt network geometry. Many studies have estimated the V m of coreforming melts in silicate (15,27,41,42,(44)(45)(46)(47)(48), and n ranging from 1 to 3.8 was proposed (42,47). Accordingly, the estimated V m varies by orders of magnitude.…”
Section: Time Scale Of Stress-induced Percolation As a Core Formation...mentioning
confidence: 99%
“…The common artefacts due to motions consisted of ring artefacts (e.g. Koeberl et al, 2002;Wang et al, 2011;Gharbi & Blunt, 2012;Mirone et al, 2014;Berg et al, 2018;Kastner & Heinzl, 2018), image 'blurriness', shading and 'triple-point' (or the so-called 'Mercedes') structures [Fig. 4(b)].…”
Section: Xrt Acquisition and Reconstructionmentioning
confidence: 99%
“…Philippe et al (2016) andA ´lvarez-Murga et al (2017) suggested its potential to image samples in situ at simple shear strain of > 2 or > 3. It has been employed for studying metallic phase transitions and melt percolation (Berg et al, 2018) at high pressure and temperature, but without the use of controlled deformation.…”
Section: Introductionmentioning
confidence: 99%